On the representation of visions in Coptic hagiographical texts - Agar, C (2022)
My thesis examines the functions of visions of heavenly beings in Coptic hagiography and their relationship to the cult of saints in Egypt. I use six saints’ hagiographical traditions as case studies: Kollouthos, Menas, Phoibammon of Preht, Merkourios, Viktor, son of Romanos, and James the Persian. My source base includes all the Coptic hagiographical texts in these saints’ traditions which contain visions experienced by them prior to their deaths and/or visions of them appearing posthumously to laypeople. I am thus able to understand the functions of visions through the writers’ choices in presenting them, and through that how they were perceived and utilised within the cult of saints.